تمرینات خاصة لتطویر التحرك بدون كرة في الهجوم المنظم للاعبین الناشئین بكرة السلة - بشار عبد اللطيف هاتف (physical education and sport sciences college for women/ Baghdad University, 2016)
The research aims to develop specific exercises to develop the move without the ball in the offensive players budding basketball, and identified research sample Ballaibn rookies in the Sports Club of Hilla and hired a researcher with some tools and equipment assistance to help him in the completion of the search, and adopted researcher curriculum prepared by the coach, and through this approach has Researcher The proposed introduction of special exercises within the practical side of the training unit, took the curriculum (6 weeks) starting from 03/02/2015 until 04/13/2015, and by (4) educational units per week, and that the most important conclusions reached by the researcher are: to exercise a positive influence for the development of moving without the ball in the attack organized basketball for young players to experimental research group, the most important researcher recommends the use of special exercises in the development of moving without the ball in the organized attack of the young basketball players.